Evaluating the Effectiveness of WhatsApp Applications in Enhancing Oral Health Awareness Among Students (Shanti Journal, 2024)
Mobile messaging apps like WhatsApp are popular communication tools, especially among youth. Oral health issues are common among young adults, but traditional education methods often fail to engage them effectively. Research on using WhatsApp for oral health education is limited, particularly in Nepal. This study aims to evaluate WhatsApp’s effectiveness in improving oral health awareness and practices among students. Employing a quantitative approach with a pretest-posttest design, the study evaluated the effectiveness of a WhatsApp intervention on oral health knowledge and practices. Conducted at Yeti Health Science Academy, 38 students participated, completing pre- and post-tests. Instruments included socio-demographic data and the Digital Education (DE) questionnaire, alongside the Oral Health Awareness and Practice questionnaire. Reliability tests indicated high consistency in the tools. Ethical approval was obtained, and descriptive and paired statistics were applied in the analysis. The mean age was 20.65, with 80% female and 90% Hindu participants. Brahmin and Chhetri were the most common ethnicity. 76.3% practiced oral hygiene, and 26.3% flossed daily. Most consumed sugar snacks (76.3%), with some experiencing dental visit anxiety (37.8%). Mouthwash was popular (89.2%), but no probiotic therapy was reported. Post-test oral health scores significantly improved (88.6579 vs. 76.9737). WhatsApp intervention shows potential in improving oral health awareness and practices among students. Integrating mobile apps like WhatsApp into oral health education programs can enhance engagement and effectiveness.